Socio-environmental aspects affecting water contamination in an urban area - Sánchez-Gutiérrez, Rolando (2021)
The purpose of the research was to identify and analyze the most relevant socio-environmental aspects causing contamination of water resources in an urban area. The study used descriptive research with a mixed approach, in which, through the collection of primary and secondary information, data was obtained related to socio-environmental perception, change patterns in land use, identification of potential sources of water contamination by discharge, and the current condition of wastewater management in the area. The information was obtained through a preliminary perception survey, field verification, satellite images, databases from regulatory authorities, and other sources. The surveyed population’s perception regarding water supply is satisfactory; however, no interest was perceived regarding home wastewater management. The analysis of land use showed a progressive increase in the use of urban land and a decrease in the use of forest areas over the last years. In addition, over 230 potential sources of water contamination were found between direct and indirect discharges. Regarding regulated discharges, the operational reports showed compliance with national regulation, even though the net organic load was high. The commercial activities and urban development negatively affect the area and accelerate water pollution. Therefore, water bodies are under constant pressure, which must be managed using participatory processes with an integrated management approach.